Answers

The Brainliest Answer!
  • Brainly User
2014-08-03T14:31:44+05:30
5(-3x-2)-(x-3)=-4(4x+5)+13
-15x-10-x+3=-16-20+13
-15x+16x-x=-20+13+10-3(we will shift the numbers one side and variables another side)
x-x=-7+7
=0
(x and x will get cancelled)

verification
5(-3 *0-2)-(0-3)=-4(4*0+5)+13
-10+3=-20+13
-7=-7
hence proved
2 5 2
mark besr
Thank You Very Much!!
hey plz mark best i need it
2014-08-03T16:38:13+05:30
5(-3x-2)-(x-3)=-4(4x+5)+13
-15x-10-x+3= - 16x-20+13
-16x-7=-16x-7
After  cancelation
The result is 0
1 5 1